2017
DOI: 10.5846/stxb201607301560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificially restored forests on soil organic carbon and active organic carbon in eroded red soil

Abstract: 收稿日期:2016• 07• 30; 修订日期:2016• 11• 04 * 通讯作者 Corresponding author.E•mail: huangrz@ nit.edu.cn DOI: 10.5846 / stxb201607301560 朱丽琴,黄荣珍,段洪浪,贾龙,王赫,黄诗华,易志强,张文锋.红壤侵蚀地不同人工恢复林对土壤总有机碳和活性有机碳的影响.生态学报,2017, 37(1) :249• 257. Zhu L Q, Huang R Z, Duan H L, Jia L, Wang H, Huang S H, Yi Z Q, Zhang W F.Effects of artificially restored forests on soil organic carbon and active organic carbon in eroded red soil.Acta Ecologica Sinica,2017,37(1) :249• 257.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…We found that SAP and OM are better than the control for increasing TOC content in 0-20 and 40-50 cm soil layers by improving the soil structure and water retention, thus promoting root (Morris et al, 2006) and microbial (Lovell et al, 1995;Joshua et al, 1999) activity. In the 0-55 cm soil layer, the AOC content of soil was ranked as SAP > OM > control, which suggests that although AOC is easily transported following rain or irrigation into the deeper soil (Zhu et al, 2017), large amounts of AOC remained in the 0-40 cm soil layer due to retention and physical protection and sorption by SAP. However, SAP and OM were conducive to the preservation of organic carbon or for carbon sinks at 10-20 cm and 40-50 cm.…”
Section: Discussionmentioning
confidence: 98%
“…We found that SAP and OM are better than the control for increasing TOC content in 0-20 and 40-50 cm soil layers by improving the soil structure and water retention, thus promoting root (Morris et al, 2006) and microbial (Lovell et al, 1995;Joshua et al, 1999) activity. In the 0-55 cm soil layer, the AOC content of soil was ranked as SAP > OM > control, which suggests that although AOC is easily transported following rain or irrigation into the deeper soil (Zhu et al, 2017), large amounts of AOC remained in the 0-40 cm soil layer due to retention and physical protection and sorption by SAP. However, SAP and OM were conducive to the preservation of organic carbon or for carbon sinks at 10-20 cm and 40-50 cm.…”
Section: Discussionmentioning
confidence: 98%